Performance study of ad hoc on-demand distance vector (AODV) for ad hoc wireless networks - Zhang, Mingjiong (2008)
An ad hoc wireless network is a network composed of mobile communication devices, which is designed to provide communication capability to satisfy the need of a temporary nature in an infrastructure-less environment. A routing protocol is necessary in ad hoc networks to ensure effective communication among nodes. This thesis presents a simulation-based study on the performance evaluation of Ad hoc on-demand distance vector (AODV) routing protocol, which is one of the core routing protocols being promoted by the Mobile Ad Hoc Networking (MANET) group of the Internet Engineering Task Force.